Preparation method of calcium modified ferrihydrite and application of calcium modified ferrihydrite in improvement of soil structure

Calcium-modified iron ore is prepared through calcium ion replacement and multi-step water washing purification technology, which solves the problem of inhibiting agglomeration effect caused by the occupancy of the sites of the unity Na+ and K+ ions, and achieves more efficient improvement in the stability and cost of soil agglomerates reduce.

CN119120027APending Publication Date: 2024-12-13HOHAI UNIV
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411186531.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

In the prior art, when artificially synthesizing iron ore, the unity Na+ and K+ ions occupy the surface binding sites, resulting in the inhibition of the agglomeration effect. During the purification process, high-speed centrifuges or flammable hazardous chemicals are required, which increases cost and safety risks.

Method used

Calcium ions are used to replace the unity Na+ and K+ ions, and the purification modification process of preliminary water washing, calcium ion exchange salt washing, and re-washing, the salt impurities in the iron ore are removed to prepare calcium modified iron ore.

Benefits of technology

It enhances the aggregation capacity of iron ore for soil particles, improves the stability of soil agglomerates, reduces purification costs and water resource consumption, and avoids the risk of using high-speed centrifuges and flammable hazardous chemicals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119120027A_ABST
    Figure CN119120027A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of calcium-modified ferrihydrite and application of the calcium-modified ferrihydrite in improvement of a soil structure, and belongs to the technical field of soil structure improvement. The preparation method of the modified ferrihydrite comprises the following steps: gradually adding a sodium hydroxide solution into a ferric trichloride solution, and stirring and mixing until the pH value of a suspension reaches neutral; aging the suspension at room temperature for 12 hours, centrifuging to remove supernate, and washing the synthesized ferrihydrite with pure water for 2-3 times; then adding a calcium chloride solution for salt washing for 2-3 times so as to fully replace sodium ions on the surface of ferrihydrite into calcium ions; and washing with pure water for 2-3 times to obtain the calcium modified ferrihydrite. The calcium modified ferrihydrite provided by the invention eliminates the influence of dispersive sodium ions or potassium ions in ferrihydrite synthesized by a traditional method, is a nanoscale weak crystalline mineral, has the effect of rapidly improving the stability of soil aggregates, can rapidly aggregate soil particles after being applied to soil, effectively enhances the structural stability of the soil, and improves the soil quality. Therefore, good materials and means can be provided for soil structure improvement.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of soil structure improvement, and particularly relates to a preparation method of calcium-modified ferrihydrite and an application thereof in improving soil structure. Background Art

[0002] Soil structure or aggregate structure is the main habitat for the growth and reproduction of soil microorganisms and protozoa. It is an important place for soil nutrient circulation and water, salt, gas and heat migration, transportation and exchange. It is also a critical organic carbon reservoir. A good and stable soil aggregate structure has an important impact on many fields such as soil carbon sequestration and emission reduction, soil erosion prevention and control, improvement of arable land quality and protection of soil biodiversity. It is the key material basis for soil to maintain high-quality soil health and ecological and environmental functions. Therefore, how to effectively enhance the stability of soil aggregate structure is an important scientific and technological issue in the field of degraded land improvement and improvement of medium and low-yield field fertility.

[0003] Ferrihydrite is a hydrated oxide naturally present in the soil. Its particles are very small, with a large specific surface area, many binding sites, and high surface energy. It also has a high isoelectric point and can carry a large amount of positive charge. Therefore, it can promote the formation of soil aggregates by virtue of the electrostatic attraction between it and the negatively charged soil particles. It is an efficient aggregate cementing material. However, the content of ferrihydrite in natural soil is low, and there is little output of ferrihydrite mineral resources. The large-scale application of ferrihydrite in fields such as soil structure improvement can only be achieved through artificial synthesis. Artificially synthesized ferrihydrite is usually obtained by a hydration chemical reaction between a trivalent iron aqueous solution and a monovalent alkali aqueous solution. However, the binding sites on the surface of the ferrihydrite prepared by this method are mainly occupied by monovalent sodium ions (Na + ) or potassium ion (K + ) is occupied. Due to the unit price Na + Ions and K + Ions have strong dispersion ability and occupy the monovalent Na + Ions and K + Ions can counteract the agglomeration effect of ferrihydrite on soil particles. For example, high content of Na + Ions are the fundamental reason why saline-alkali soil has extremely strong dispersion. + Ions and K + Due to the strong dispersibility of ions, the ferrihydrite colloid synthesized by this method has a high degree of dispersion and is difficult to purify. It will contain more sodium or potassium salt impurities and requires a large amount of pure water or alcohol to purify it, or requires the use of special equipment such as high-speed centrifuges and electrodialysis.

[0004] For example, patents CN117772126A, CN108686624A and CN111018088A respectively disclose a method for preparing modified or functionalized ferrihydrite. In these three patents, the synthesis of ferrihydrite is carried out by using ferric chloride (FeCl 3 ) or ferric nitrate (Fe(NO 3 ) 3 ) aqueous solution and sodium hydroxide (NaOH) or potassium hydroxide (KOH) aqueous solution as raw materials for synthesis. After the synthesis of ferrihydrite colloid, pure water is also used to wash and centrifuge the synthetic ferrihydrite. However, when only pure water is used for purification, due to the Na + and K + Due to the strong dispersibility of ions, even with a high-speed centrifugation of 5000rpm / min, the ferrihydrite suspension can only be purified to a conductivity of 2000-4000μS / cm. At this conductivity, the synthetic ferrihydrite suspension still contains about 1.5-4g / kg of Na salt or K salt impurities. Although the use of high-speed centrifugation, alcohol washing purification or electrodialysis can further reduce the content of sodium and potassium impurities, this requires special equipment or the use of flammable hazardous chemicals, which will inevitably greatly increase the purification cost and safety risks. More importantly, the above methods can only remove part of the soluble Na in the ferrihydrite colloidal suspension. + or K + ions, but cannot remove the Na + or K + Ion. Dispersible Na + or K + The counteracting effect of ions on the agglomeration effect of ferrihydrite still exists, which will still greatly inhibit the improvement effect of ferrihydrite on soil structure. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing calcium-modified ferrihydrite in view of the shortcomings of the prior art. The present invention can modify the dispersed Na + , K + Ion replacement with calcium ions (Ca) which have bridging and cohesive properties 2+ ), and can also save time and effort to remove salt impurities from ferrihydrite without using a high-speed centrifuge, electrodialysis device or ethanol, with better purification effect, less water consumption and lower cost.

[0006] The present invention also aims to provide an application of calcium-modified ferrihydrite in improving soil structure.

[0007] To achieve the above object, the present invention adopts the following technical solutions:

[0008] The calcium-modified nano-ferrihydrite of the present invention is made from the following raw materials:

[0009] 0.3~0.6mol FeCl 3 6H 2 O aqueous solution, 1-2 mol NaOH aqueous solution, 2-4 mol calcium chloride (CaCl 2 ) aqueous solution.

[0010] Preferably, it is prepared from the following raw material ratio: 1 to 2 L of 0.3 mol / L FeCl 3 6H 2 O aqueous solution, 1-2 L of 1 mol / L NaOH aqueous solution, 4-8 L of 0.5 mol / L CaCl 2 Aqueous solution.

[0011] The present invention provides a method for preparing the calcium-modified nano-ferrihydrite described in the above scheme, comprising the following steps:

[0012] S1. Slowly pour 1-2L of 1mol / L NaOH aqueous solution into 1-2L of 0.3mol / L FeCl 3 6H 2 O aqueous solution into a 5L beaker, stirring with a stirring rod until the pH of the suspension reaches the neutral range:

[0013] S2, aging the suspension obtained in step S1 at room temperature, centrifuging at a speed of 2000 rpm / min after the aging time is reached, and removing the supernatant to obtain a ferrihydrite centrifugal precipitate;

[0014] S3, transfer the ferrihydrite precipitate obtained in step S2 to a clean 5L beaker, add 3-4L pure water, stir and disperse with a stirrer, centrifuge again, remove the supernatant, and repeat this step 2-3 times until the conductivity of the ferrihydrite colloidal suspension is reduced to 3000-5000μS / cm;

[0015] S4. Transfer the ferrihydrite precipitate washed with water in step S3 to another clean 5L beaker and add 2-3L of 0.5mol / L CaCl 2 The aqueous solution is stirred for 3 to 5 hours, and then centrifuged at a speed of 2000 rpm / min to remove the supernatant. The centrifugal precipitate obtained after repeating this step 2 to 3 times is the calcium ion-modified salt water iron ore;

[0016] S5, transferring the centrifugal precipitate after salt washing in step S4 to a 5L beaker, adding 3-4L pure water, stirring and dispersing with a stirrer, centrifuging, removing the supernatant, and repeating this step until the conductivity of the ferrihydrite colloidal suspension is less than 500μS / cm, thereby obtaining the colloidal calcium-modified ferrihydrite of the present invention;

[0017] S6. The colloidal calcium-modified ferrihydrite obtained in step S5 is freeze-dried or low-temperature dried, and then ground into powder to prepare powdered calcium-modified ferrihydrite.

[0018] Preferably, the neutral pH range of the suspension is 6.9 to 7.2.

[0019] Preferably, the room temperature condition is 20-30°C.

[0020] Preferably, the static aging time is 12 to 48 hours.

[0021] Preferably, the electrical conductivity is lower than 500 μS / cm and is 200-500 μS / cm.

[0022] Preferably, the colloidal calcium-modified ferrihydrite should be prepared and used immediately, and the effective storage time is 1 to 2 weeks.

[0023] Preferably, when the calcium-modified ferrihydrite is used, the effect of the colloidal calcium-modified ferrihydrite is better than that of the powdered calcium-modified ferrihydrite.

[0024] The present invention also provides application of the calcium-modified ferrihydrite or the calcium-modified ferrihydrite obtained by the preparation method in improving soil structure.

[0025] Preferably, the soil includes agricultural land soil and non-agricultural land soil, agricultural land includes newly renovated cultivated land and / or medium and low-yield fields, and non-agricultural land includes natural land prone to soil erosion and production and construction land.

[0026] Preferably, the pH value of the soil is below 9.0.

[0027] Based on the above technical solution, the calcium-modified ferrihydrite of the present invention has the following characteristics and technical advantages:

[0028] 1. The calcium-modified ferrihydrite provided by the present invention eliminates a large amount of dispersed Na contained in the ferrihydrite synthesized by the traditional method. + or K + ions and will occupy the dispersed Na + or K + Ion replacement with Ca which has cationic bridging function and cohesive ability 2+ ions, thereby enhancing the ability of ferrihydrite to aggregate soil particles, promoting the formation of large soil aggregate structures and improving their stability. The effect of calcium-modified ferrihydrite on improving the stability of soil aggregates is better than that of sodium ferrihydrite or potassium ferrihydrite synthesized by traditional methods.

[0029] 2. The binding site on the surface of the calcium-modified ferrihydrite provided by the present invention is Ca with cationic bridging ability.2+ ions, thereby combining ferrihydrite with humic acid through a bridging effect, so that when calcium-modified ferrihydrite and humic acid are applied in combination, the stability of soil aggregates can be better improved.

[0030] 3. In the preparation method of calcium-modified ferrihydrite provided by the present invention, a purification and modification process of "preliminary water washing → calcium ion exchange salt washing → water washing again" is adopted for the crude ferrihydrite containing sodium salt obtained after preparation, and the salt content of the synthetic ferrihydrite can be reduced to a range suitable for soil improvement without the use of special devices such as high-speed centrifuges and electrodialysis. Compared with the traditional purification process of only washing with water, the purification and modification process provided by the present invention has the advantages of higher purification efficiency, better effect, water resource conservation, and more time-saving and labor-saving operation. At the same time, the process adopted by the present invention does not need to use alcohol to purify the ferrihydrite, and compared with the purification process of pure water washing and then using alcohol, the cost is lower, and the adverse effects of flammable hazardous chemicals alcohol on production safety are avoided.

[0031] 4. The colloidal calcium-modified ferrihydrite of the present invention has fine particles, with a particle size of only about 20 nm, and is a nano-scale weakly crystalline mineral with a large specific surface area and high surface reactivity, thereby having the ability to quickly improve soil structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is the color comparison of the supernatant during the purification process of ferrihydrite pure water and alcohol;

[0033] Figure 2 X-ray diffraction (XRD) patterns of ferrihydrite prepared by different processes;

[0034] Figure 3 X-ray diffraction (XRD) patterns of ferrihydrite synthesized or modified with different ions;

[0035] Figure 4 The X-ray diffraction (XRD) patterns of the long-standing colloidal and powdered calcium-modified ferrihydrite;

[0036] Figure 5 The appearance photos of colloidal and powdered calcium-modified ferrihydrite are shown;

[0037] Figure 6 This is a scanning electron microscope photo of colloidal calcium-modified ferrihydrite;

[0038] Figure 7 The experimental results of different types of ferrihydrite on the improvement of soil structure;

[0039] Figure 8 These are the experimental results on the improvement of soil structure by applying different types of ferrihydrite and humic acid. DETAILED DESCRIPTION

[0040] The present invention provides a method for preparing calcium-modified ferrihydrite, which is prepared from the following raw materials:

[0041] 0.3~0.6mol FeCl 3 6H 2 O aqueous solution, 1-2 mol NaOH aqueous solution, 2-4 mol CaCl 2 Aqueous solution.

[0042] In the present invention, the calcium ion modified nano ferrihydrite is preferably prepared by the following raw material ratio: 1 to 2 L of 0.3 mol / L FeCl 3 6H 2 O aqueous solution, 1-2 L of 1 mol / L NaOH aqueous solution, 5-7 L of 0.5 mol / L CaCl 2 Aqueous solution. More preferably, 1L of 0.3mol / L FeCl 3 6H 2 O aqueous solution, 1L of 1mol / L NaOH aqueous solution, 6L of 0.5mol / L CaCl 2 Aqueous solution.

[0043] The present invention provides a method for preparing the calcium-modified ferrihydrite, comprising the following steps:

[0044] S1. Slowly pour 1-2L of 1mol / L NaOH aqueous solution into 1-2L of 0.3mol / L FeCl 3 6H 2 O aqueous solution into a 5L beaker, stirring with a stirring rod until the pH of the suspension reaches the neutral range;

[0045] S2, aging the suspension obtained in step S1 at room temperature, centrifuging at a speed of 2000 rpm / min after the aging time is reached, and removing the supernatant to obtain a ferrihydrite precipitate;

[0046] S3, transfer the ferrihydrite precipitate obtained in step S2 to a 5L beaker, add 3-4L pure water, stir and disperse with a stirrer, centrifuge again, remove the supernatant, and repeat this step 2-3 times until the conductivity of the ferrihydrite colloidal suspension is reduced to 3000-5000μS / cm;

[0047] S4. Transfer the ferrihydrite centrifugal precipitate after washing in step S3 to another clean 5L beaker and add 2-3L of 0.5mol / L CaCl 2 The aqueous solution is stirred for 3 to 5 hours, and then centrifuged at a speed of 2000 rpm / min to remove the supernatant. The centrifugal precipitate obtained after repeating this step 2 to 3 times is the calcium ion-modified salt water iron ore;

[0048] S5, transferring the centrifugal precipitate after salt washing in step S4 to a 5L beaker, adding 3-4L pure water, stirring and dispersing with a stirrer, centrifuging, removing the supernatant, and repeating this step until the conductivity of the ferrihydrite colloidal suspension is less than 500μS / cm, thereby obtaining the colloidal calcium-modified ferrihydrite of the present invention;

[0049] S6. The colloidal calcium-modified ferrihydrite obtained in step S5 is freeze-dried or low-temperature dried, and then ground into powder to prepare powdered calcium-modified ferrihydrite.

[0050] In the present invention, the pH is adjusted to a neutral range of 6.5 to 7.5, preferably 6.9 to 7.2, and most preferably 7.0. The room temperature conditions described in the present invention have a temperature range of 15 to 40°C, preferably 20 to 30°C, and most preferably 25 to 28°C. The conductivity of the ferrihydrite colloidal suspension described in the present invention is lower than 500 μS / cm, preferably 200 to 500 μS / cm, and most preferably 350 μS / cm. The CaCl 2 The concentration of the aqueous solution is 0.1-3 mol / L, preferably 0.3-1 mol / L, and most preferably 0.5 mol / L. At the same time, the present invention also adjusts the parameters such as the aging time, the method of adjusting the pH to neutrality, and the solution concentration during the preparation process, and selects aging for 24h or 48h, directly adjusting the pH to neutrality or adjusting to alkalinity and then to neutrality, and using different concentrations of aqueous solutions during preparation. The results show that the X-ray diffraction patterns of the samples prepared under different aging times (24h and 48h), pH adjustment methods (from acidic to neutral and from acidic to alkaline to neutral) and different concentrations all show relatively obvious broad peaks near 35° and 62°. These two peaks are basically consistent with the diffraction pattern of 2-line ferrihydrite, indicating that all the ferrihydrite prepared under these conditions will not change due to aging time, pH adjustment method or aqueous solution concentration.

[0051] In the present invention, the particle size of the colloidal calcium-modified ferrihydrite is about 20 nm, which is much smaller than the powdered nano ferrihydrite passing through a 300-mesh sieve. Therefore, when calcium-modified ferrihydrite is used to improve soil structure, colloidal calcium-modified ferrihydrite is better than powdered calcium-modified ferrihydrite. At the same time, the present invention performs X-ray diffraction (XRD) pattern analysis on colloidal ferrihydrite samples that have been stored for 8 months and finds that it has aged and turned into other crystalline iron oxides. Therefore, colloidal calcium-modified ferrihydrite should be prepared and used as soon as possible, and the storage time should be within 1 to 2 weeks as much as possible.

[0052] In the present invention, potassium hydroxide (KOH) alkaline solution or calcium carbonate (CaCO 3) was used to replace NaOH alkaline solution to prepare ferrihydrite. The results showed that the XRD pattern of the sample prepared with KOH solution was basically consistent with the diffraction pattern of 2-line ferrihydrite, indicating that the sample prepared under this condition was also ferrihydrite. 3 The XRD spectrum of the prepared sample has diffraction peaks at angles of 35° and 62°, as well as other diffraction peaks, indicating that CaCO 3 The ferrihydrite used to prepare the ferrihydrite has more impurities.

[0053] The invention provides application of the calcium-modified ferrihydrite in improving soil structure.

[0054] In the present invention, the above-mentioned application method of the calcium-modified ferrihydrite preferably comprises the following steps:

[0055] 1) Apply the colloidal calcium-modified ferrihydrite as described above to the soil to be improved.

[0056] 2) Evenly turn the applied calcium-modified ferrihydrite into the soil surface or tillage layer to be improved.

[0057] The soil to be improved includes agricultural land soil and non-agricultural land soil. Agricultural land includes newly renovated cultivated land and / or medium and low-yield fields, and non-agricultural land includes natural land prone to soil erosion and production and construction land.

[0058] The pH value of the soil to be improved should be less than 9.0, preferably less than 8.5.

[0059] Wherein, the application method includes mechanical application and manual application.

[0060] The application amount of the calcium-modified ferrihydrite is recommended to be between 50 and 200 kg / mu.

[0061] Wherein, the thickness of the soil surface layer or the tillage layer is 15 to 20 cm.

[0062] The calcium-modified ferrihydrite can be applied together with humic acid, straw, etc., and supplemented with nitrogen and phosphorus nutrients.

[0063] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

[0064] The preparation method of calcium-modified ferrihydrite provided by the present invention and its application in improving soil structure are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0065] Example 1

[0066] Comparison of water purification and alcohol purification of ferrihydrite

[0067] Take 1 mol / L NaOH aqueous solution and slowly pour it into 1L 0.3 mol / L FeCl 3 6H 2 O aqueous solution, stirring while adding until the pH of the suspension reaches 7.0; place the suspension at room temperature for 12 hours and then centrifuge to obtain ferrihydrite precipitate; add 2 to 3L of pure water to the precipitate, stir thoroughly and centrifuge again, repeat this step until it cannot be completely centrifuged at a speed of 5000rpm / min for 20 minutes. Figure 1 The supernatant in a is turbid. The conductivity of the supernatant is 2000-4000 μS / cm. Then add 1-2L of 95% alcohol and stir thoroughly to make the supernatant clear again. Figure 1 As shown in b; repeating the above purification step of adding alcohol, the conductivity of the supernatant can be washed to below 50μS / cm.

[0068] In Example 1, a large amount of Na + ions, so it needs to be purified. Usually, the purification method of pure water washing and centrifugation is used to reduce the conductivity of the ferrihydrite suspension to 2000-4000μS / cm. However, the use of high-purity alcohol can further reduce the conductivity of the ferrihydrite suspension to less than 50μS / cm. At this time, the soluble Na + The ion content is low.

[0069] Example 2

[0070] Purification of calcium-modified ferrihydrite by washing

[0071] Take 1 mol / L NaOH aqueous solution and slowly pour it into 1L 0.3 mol / L FeCl 3 6H 2 O aqueous solution, stirring until the pH of the suspension reaches 7.0, aging the suspension at room temperature for 12 hours and then centrifuging to obtain ferrihydrite precipitate; adding 2-3L pure water to the precipitate, stirring thoroughly and centrifuging again; after repeating this step 3 times, the supernatant will become turbid during centrifugation; at this time, add 2L 0.5mol / L CaCl 2 The aqueous solution is stirred for 3 to 5 hours and then centrifuged to remove the supernatant; after repeating this step 3 times, the precipitate obtained is the calcium-modified salt-containing ferrihydrite. Then pure water is added for water washing and centrifugal purification. At this time, even if the conductivity of the ferrihydrite suspension is lower than 500μS / cm, the supernatant after centrifugation is still clear, indicating that water washing and purification can be continued to make the conductivity and salt content of the ferrihydrite suspension lower.

[0072] In Example 2, the Na + After washing away most of the ions, use Ca 2+ Ion replacement of Na on the surface of ferrihydrite + ions, and then use pure water to continue to purify the calcium-containing salt water iron ore to remove excess Ca 2+ ions, the effect of alcohol purification in Example 1 can be achieved. Taking into account the cost, time and safety issues, the alcohol purification process can be replaced by using Ca 2+ Ionic solution replaces Na on the surface of ferrihydrite + After the ions are separated, a purification process is performed by washing and purification.

[0073] Example 3

[0074] Effects of different aging time, pH adjustment methods and aqueous solution concentration on the preparation of nano-ferrihydrite

[0075] Take 1L 0.3mol / L FeCl 3 6H 2 3 portions of 1mol / L NaOH aqueous solution were added to the suspension by stirring, and the pH value of the suspension was gradually adjusted from the initial acidity to 7.0 in two portions, and the suspension was aged for 24 and 48 hours at room temperature and then centrifuged; the obtained ferrihydrite precipitates were washed with pure water for 2 to 3 times, and then purified with 95% alcohol for 1 to 2 times until the conductivity of the ferrihydrite was less than 500μS / cm, and ferrihydrite No. 1 and No. 2 were obtained respectively. The pH value of the remaining suspension was first adjusted to alkaline 9.0 with 1mol / L NaOH aqueous solution, and then adjusted back to neutral 7.0 with hydrochloric acid solution; the suspension was aged for 24 hours at room temperature and then centrifuged; the obtained ferrihydrite precipitates were washed with pure water for 2 to 3 times and then purified with 95% alcohol for 1 to 2 times until the conductivity of the ferrihydrite suspension was less than 500μS / cm, and the obtained sample was ferrihydrite No. 3.

[0076] Take 1L 1mol / L FeCl 3 6H 2 1 part of 1mol / L NaOH aqueous solution was added while stirring until the pH of the suspension reached 7.0; the suspension was allowed to stand and age for 24h at room temperature and then centrifuged; the obtained ferrihydrite precipitate was washed with pure water for 2-3 times and then purified with 95% alcohol for 1-2 times to make the conductivity of the ferrihydrite suspension lower than 500μS / cm. The obtained sample was No. 4 ferrihydrite.

[0077] The ferrihydrite No. 1-4 synthesized in Example 3 was dried at low temperature (<60°C), ground and sieved, and subjected to XRD phase analysis. Figure 2From the XRD patterns of ferrihydrite samples No. 1-4, it can be seen that the diffraction patterns of ferrihydrite samples treated with different aging times, different pH adjustment methods and aqueous solution concentrations are almost the same, and all show relatively obvious broad peaks near the diffraction angles of 35° and 62°. These two peaks are basically consistent with the diffraction pattern of 2-line ferrihydrite, which shows that samples No. 1-4 are all ferrihydrite, and the three experimental conditions will not affect their preparation. Therefore, when preparing ferrihydrite in large quantities, in order to save time and material costs, a 1:3 Fe 3+ / Na + The concentration ratio is mixed to neutral and then left to age.

[0078] Example 4

[0079] Preparation method of ferrihydrite synthesized or modified by different ions

[0080] Take 1L 1mol / L FeCl 3 6H 2 O aqueous solution, one of which was stirred while adding 3 mol / L KOH aqueous solution, and the pH of the suspension was adjusted to 7.0, and then aged for 12 hours at room temperature, and then centrifuged and washed until the conductivity of the suspension was lower than 500 μS / cm, to obtain KOH synthetic ferrihydrite (potassium ferrihydrite). Two other parts were stirred while adding 3 mol / L NaOH solution, and the pH of the suspension was adjusted to 7.0, and then aged for 12 hours at room temperature, and then one of them was washed with pure water until the conductivity was lower than 500 μS / cm, to obtain NaOH synthetic ferrihydrite (sodium ferrihydrite), and the other was first washed with pure water by centrifugation until the conductivity was less than 1000 μS / cm, and then washed with CaCl 2 The solution was washed twice with salt, and finally washed with pure water by centrifugation until its conductivity was less than 500 μS / cm to obtain CaCl 2 Synthetic ferrihydrite (calcium modified ferrihydrite). The last part of FeCl 3 6H 2 O aqueous solution was added with stirring while adding CaCO 3 Powder, due to CaCO 3 Due to its low alkalinity and solubility, the pH of the suspension can only be adjusted to 5.5. Therefore, after the pH of the suspension is adjusted to 5.5, it is aged at room temperature for 12 hours, and then centrifuged until the conductivity is less than 100 μS / cm to obtain CaCO 3 Synthetic ferrihydrite.

[0081] The four ferrihydrite samples synthesized in Example 4 were subjected to XRD phase analysis. Figure 3 The XRD patterns of the four samples show that no matter NaOH, KOH or Ca 2+The synthesized samples are all ferrihydrite, and all three exhibit characteristic peaks of 2-line ferrihydrite near the diffraction angles of 35° and 62°, indicating that the purity of the ferrihydrite of the three is relatively high. 3 The extracted samples have other peaks besides the characteristic peaks at 35° and 62° diffraction angles, indicating that CaCO 3 The purity of ferrihydrite in the extracted sample is not high.

[0082] Example 5

[0083] Calcium-modified ferrihydrite will denature if left for a long time.

[0084] Take 1L 1mol / L FeCl 3 6H 2 O aqueous solution was stirred and 3 mol / L NaOH aqueous solution was added until the pH of the suspension reached 7.0, and then the suspension was aged at room temperature for 12 h; the suspension was centrifuged and washed with water three times, and then washed with CaCl 2 The solution was washed with salt twice, and then centrifuged with pure water until the conductivity of the ferrihydrite suspension was less than 500 μS / cm to obtain a colloidal calcium-modified ferrihydrite sample; the obtained colloidal calcium-modified ferrihydrite sample was divided into two equal parts, one of which was immediately dried at low temperature (<60°C), ground and sieved, and stored for 8 months; the other colloidal calcium-modified ferrihydrite was always sealed and stored in a colloidal state at room temperature, and after 8 months of storage, it was dried at low temperature and ground and sieved.

[0085] Phase analysis was performed on the two calcium-modified ferrihydrite samples synthesized in Example 5. Figure 4 It can be seen from the XRD spectrum that the colloidal calcium-modified ferrihydrite has been completely aged and turned into crystalline iron oxide after long-term storage. The aged iron oxide is composed of 84% goethite and 16% hematite. However, the calcium-modified ferrihydrite that was dried immediately is still weakly crystalline ferrihydrite after being stored for 8 months. Therefore, colloidal calcium-modified ferrihydrite is not easy to preserve. It is best to prepare it for immediate use or prepare it into powdered ferrihydrite for long-term storage.

[0086] Example 6

[0087] Morphological Characterization of Colloidal and Powdered Calcium-Modified Ferrihydrite

[0088] Take 1L 1mol / L FeCl 3 6H 2 O aqueous solution, add 3 mol / L NaOH aqueous solution while stirring until the pH of the suspension reaches 7.0; place the suspension at room temperature for 12 hours, then centrifuge and wash with water three times, and then use CaCl 2The solution was washed twice with salt, and then the conductivity of the ferrihydrite suspension was washed with pure water to less than 500 μS / cm to obtain a colloidal calcium-modified ferrihydrite sample; the colloidal calcium-modified ferrihydrite sample was divided into two equal parts, one of which was immediately dried at low temperature and ground through a 300-mesh sieve to obtain powdered calcium-modified ferrihydrite, and the other part was dispersed in water to prepare a colloidal suspension, and the morphology was characterized by a scanning electron microscope.

[0089] Figure 5 The colloidal ( Figure 5 a) and powdered ( Figure 5 b) Photo of the appearance of calcium-modified ferrihydrite. Figure 6 The scanning electron microscope photos of the colloidal state at different resolutions show that the colloidal state is easily dispersible particles, and the size of a single particle is about 20nm. Compared with the powdered calcium-modified ferrihydrite particles with a mesh size of 300 (0.053μm), the particles are finer, have a larger specific surface area, and have stronger coagulation and cementation ability.

[0090] Application Example 1

[0091] Effects of different types of ferrihydrite on soil structure

[0092] This experiment selected the newly renovated cultivated loess soil in Kangping Village, Baota District, Yan'an City, Shaanxi Province (N36°44′5″, E109°34′28″) as the experimental object. The organic matter and nutrient content of this soil is extremely low, with only 2.10g / kg of organic matter, very poor nutrients, pH up to 8.8, and the soil texture is silt loam, of which sand particles are 66.8%, silt particles are 28.4%, and clay particles are 4.8%. Its clay minerals mainly contain 32% of hydromica, 28% of kaolinite and 24% of chlorite. At the same time, the aggregate structure stability of the newly renovated loess soil is very poor, and it is not easy to form stable large aggregates.

[0093] After the land consolidation measures of the cultivated land were completed, the surface soil samples of 0-20cm were collected as experimental soil samples. The collected samples were air-dried and passed through a 2mm sieve and then bagged for use. A total of 6 treatments were set up in this part of the experiment (3 replicates were set up for each treatment), namely: ① control (CK), ② sodium hydroxide synthesized ferrihydrite (sodium ferrihydrite), ③ potassium hydroxide synthesized ferrihydrite (potassium ferrihydrite), ④ calcium ion exchange modification (calcium modified ferrihydrite), ⑤ calcium carbonate synthesized ferrihydrite. The specific experimental steps are: weigh 150g of air-dried soil sample passing through a 2mm sieve in a 1L plastic culture box, apply the above 4 ferrihydrite samples in colloidal form just prepared and purified in Example 4 at an application rate of 2%, mix evenly, add water to adjust the soil moisture content in the box to 70% of the field water holding capacity, and place it in an artificial climate incubator at 28°C for constant temperature culture for 2 weeks. During the entire culture period, water was supplemented by weighing method to maintain a constant soil moisture content. After the incubation, the soil was taken out and air-dried, and the water stability of soil aggregates from the five treatments was measured.

[0094] Figure 7 The results showed that after 2 weeks of short-term cultivation, compared with CK, both calcium-modified ferrihydrite and calcium carbonate synthetic samples significantly increased the number of 2-0.25 mm macroaggregates, with an increase of 1.05 times and 0.56 times, respectively. The improvement effect of calcium-modified ferrihydrite was better than that of calcium carbonate synthetic samples. On the contrary, sodium ferrihydrite and potassium ferrihydrite had no effect on the number of macroaggregates of >2 mm and 2-0.25 mm, and potassium ferrihydrite even significantly reduced the number of 2-0.25 mm macroaggregates. In summary, the application of calcium-modified ferrihydrite to newly renovated loess soil can significantly and quickly improve the stability of loess soil aggregates and improve its structural condition, and the improvement effect far exceeds that of sodium ferrihydrite, potassium ferrihydrite and calcium carbonate synthetic ferrihydrite samples.

[0095] Application Example 2

[0096] Effects of different types of ferrihydrite and humic acid on soil structure improvement

[0097] This application example still selects the newly renovated cultivated land soil in Application Example 1, loess soil, as the experimental object, and sets up the following 8 treatments (3 replicates for each treatment): ① control (CK), ② sodium ferrihydrate (Na + ), ③ potassium ferrihydrite (K+), ④ calcium modified ferrihydrite (Ca 2+ ), ⑤ humic acid (HA), ⑥ sodium ferrihydrate + humic acid (Na + +HA), ⑦potassium ferrihydrate + humic acid (K + +HA),⑧Calcium modified ferrihydrite + humic acid (Ca 2++HA). The specific experimental steps are consistent with those in Application Example 1, and the nano-ferrihydrite sample used is a colloidal sample that has just been prepared and purified. Humic acid is humic acid extracted from woody peat, and the addition ratio of each humic acid treatment is 0.1% of the soil mass. After the cultivation experiment is carried out according to the method of Application Example 1, the soil samples of each treatment are air-dried, and the water stability of the soil aggregates of each treatment is measured.

[0098] Figure 8 The results showed that after 2 weeks of short-term cultivation, compared with CK, only the calcium-modified ferrihydrite treatment significantly increased the number of 2-0.25 mm macroaggregates in the three treatments with only ferrihydrite added (sodium ferrihydrite, potassium ferrihydrite, and calcium-modified ferrihydrite). Only the addition of humic acid could not significantly increase the number of 2-0.25 mm macroaggregates, but the combination of HA and calcium-modified ferrihydrite greatly increased the number of macroaggregates of this size, and the increase was much greater than that of Na + +HA and K + +HA treatment. Compared with CK, the number of macroaggregates >2 mm in other treatments increased to varying degrees. Among them, in the three treatments with only ferrihydrite added (sodium ferrihydrite, potassium ferrihydrite, and calcium-modified ferrihydrite), Ca 2+ The treatment with the largest improvement was also the Ca 2+ The improvement of +HA treatment was greater. In summary, calcium-modified ferrihydrite can significantly and quickly improve the stability of soil aggregates in newly renovated cultivated land, which is much better than sodium ferrihydrite and potassium ferrihydrite, and the effect is better when applied in combination with humic acid.

Claims

1. A method for preparing calcium-modified ferrihydrite, characterized in that: The following steps are involved: Step S1, slowly adding 1 mol / L sodium hydroxide aqueous solution into a 5 L beaker containing 1-2 L 0.3 mol / L ferric chloride aqueous solution, stirring until the pH value of the suspension reaches a neutral range; Step S2, aging the suspension obtained in step S1 at room temperature for 12 to 48 hours, centrifuging, removing the supernatant, and obtaining a ferrihydrite centrifugal precipitate; Step S3, adding 3-4 L of pure water to the ferrihydrite precipitate in step S2, stirring and dispersing the mixture with a stirrer, centrifuging the mixture, removing the supernatant, and repeating this step 2-3 times until the conductivity of the suspension is reduced to an appropriate range; Step S4, adding 2 to 3 L of calcium chloride aqueous solution to the ferrihydrite precipitate washed in step S3, stirring with a stirrer for 3 to 5 hours, centrifuging, removing the supernatant, and repeating this step 2 to 3 times; Step S5, adding 3-4 L of pure water to the ferrihydrite precipitate after the salt washing in step S4, fully stirring and dispersing with a stirrer, centrifuging, removing the supernatant, and repeating this step 2-3 times to reduce the conductivity of the ferrihydrite suspension to less than 500 μS / cm, thereby obtaining the colloidal calcium-modified ferrihydrite of the present invention; Step S6, drying the colloidal calcium-modified ferrihydrite in step S5, and grinding it into powder to obtain powdered calcium-modified ferrihydrite.

2. The method for preparing calcium-modified ferrihydrite according to claim 1, characterized in that: The pH value in step S1 reaches a neutral range of 6.5 to 7.

5.

3. The method for preparing calcium-modified ferrihydrite according to claim 1, characterized in that: The room temperature condition described in step S2 is 10-40°C.

4. The method for preparing calcium-modified ferrihydrite according to claim 1, characterized in that: The conductivity of the suspension in step S3 is reduced to a suitable range, which is 2000-5000 μS / cm.

5. The method for preparing calcium-modified ferrihydrite according to claim 1, characterized in that: The calcium chloride aqueous solution described in step S4 has a concentration of 0.1 to 3 mol / L.

6. The method for preparing calcium-modified ferrihydrite according to claim 1, characterized in that: After adding water to the colloidal calcium-modified ferrihydrite described in step S5 and stirring, the colloidal calcium-modified ferrihydrite can be redispersed into micro-nano particles.

7. The method for preparing calcium-modified ferrihydrite according to claim 1, characterized in that: The drying method described in step S6 can be a freeze-drying method or a low-temperature drying method below 60°C.

8. Use of the ferrihydrite prepared according to claim 1 or the modified ferrihydrite prepared by the preparation method according to any one of claims 2 to 6 in improving soil structure.

9. The use according to claim 8, characterized in that: The soil includes agricultural land soil and non-agricultural land soil. Agricultural land includes newly renovated cultivated land and / or medium and low-yield fields, and non-agricultural land includes natural land prone to soil erosion and production and construction land.

Citation Information

Cited By

  • Application method of modifier for acidification of southern forest soil

    CN119968984A

  • A method for applying a soil amendment for acidification of southern forest soils

    CN119968984B

  • In-situ As contaminated soil heat treatment remediation method for enhancing heat efficiency

    CN120001782A

  • A method for remediation of arsenic contaminated soil by in-situ thermal treatment with enhanced thermal efficiency

    CN120001782B